The Effect of Oxytocin Massage on First-Stage Labor Pain - Wahyu Abadi Junjung Drajad; Kharisma Kusumaningtyas; Titi Maharrani; Siti Alfiah (Jurnal Ilmiah Kesehatan)
Pain during labor results from uterine contractions that cause cervical dilation, often